2019
DOI: 10.1111/ldrp.12211
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Motion Math: Bounce on Students’ Fraction Knowledge

Abstract: National assessments suggest that many students do not display proficiency with fractions. Considering that time and materials are precious resources, many educators are looking to use technology to provide supplemental instruction with low demand on the instructor. The current study utilized a multiple-baseline design to examine the effects of the Motion Math: Bounce application on the fraction quantity comparison and number line placement skills of three fifthgrade students. Results indicate that Motion Math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…More recently, SCRDs have been used to test the effects of interventions for students with a LD in a variety of areas including writing (e.g., Datchuk & Rogers, 2018; Shen & Troia, 2018), video modeling (e.g., Satsangi et al., 2019), and mathematics interventions (McKevett et al., 2020). Furthermore, systematic reviews designed to identify whether specific practices can be identified as EBPs for students with LD include SCRDs.…”
Section: Use Of Scrd In Ld Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, SCRDs have been used to test the effects of interventions for students with a LD in a variety of areas including writing (e.g., Datchuk & Rogers, 2018; Shen & Troia, 2018), video modeling (e.g., Satsangi et al., 2019), and mathematics interventions (McKevett et al., 2020). Furthermore, systematic reviews designed to identify whether specific practices can be identified as EBPs for students with LD include SCRDs.…”
Section: Use Of Scrd In Ld Researchmentioning
confidence: 99%
“…Cooper et al recommend an ordinate:abscissa ratio between 2:3 and 5:8. This recommendation, however, is not new and can be traced back to Parsonson and Baer (1978). Kubina et al (2017) selected 11 journals that publish research in the realm of behavior and randomly selected an issue every 2 years from the journal's inception up through 2011.…”
Section: The Impact Of Graph Construction On Visual Analysismentioning
confidence: 99%
“…Analysis of the content of professional journals guides the field by identifying gaps and trends in the research base (MacFarland et al, 2013). Several content analyses of special education journals were conducted recently (e.g., Gage et al, 2017; Garwood et al, 2021; Hott et al, 2018; MacFarland et al, 2013; Mastropieri et al, 2009); however, none of them examined reporting quality.…”
Section: Purpose Of the Present Studymentioning
confidence: 99%
“…Jika ditinjau darp proses belajar, Stephen & Clements (McKevett et al, 2020) menyatakan bahwa mempelajari pecahan cenderung difokuskan pada aspek prosedural dibandingkan memberikan pemahaman mendalam pada siswa. Kompleksitas pecahan menjadi bagian yang tak dapat diabaikan dalam proses pembelajaran (Eriksson & Sumpter, 2021;Lee & Hackenberg, 2014;McKevett et al, 2020), bahwa tidak ada bidang matematika di sekolah yang kaya, kompleks, dan sulit untuk diajarkan seperti pecahan.…”
Section: Pendahuluanunclassified
“…Stephen & Clements (McKevett et al, 2020) menyatakan bahwa konsep pecahan cemderung terfokus pada aspek proseduralnya dibandingkan pada konseptualnya. Hal ini berdampak pada kerumitan bagi guru untuk mengajarkan konsep tersebut (McKevett et al, 2020), bahwa tak satupun bidang dalam matematika sekolah sekaya, sekompleks, dan sesulit untuk mengajarkannya seperti pecahan.…”
Section: Diskusiunclassified